Isolated symmetrical bilateral basal ganglia T2 hyperintensity in carbon monoxide poisoning - Subhaschandra S; Jatishwor W; Th.Suraj (Annals of Indian Academy of Neurology, 2008)
Carbon monoxide poisoning is not uncommon during the winter months. To make a diagnosis, strong clinical suspicion and acumen, and history of the exposure are necessary. Many a time, the presenting complaints may fail to help reach a diagnosis, in the absence of history. Imaging plays a role in the diagnosis of brain injury with the characteristic features, which are correlated with the clinical profile. Isolated bilateral basal ganglia injury revealing T2 hyperintensity in MRI may be observed in acute carbon monoxide poisoning.